Dress Code: Identitas, Komunikasi, dan Kreativitas - Zakaria Lantang Sukirno (Journal of Tourism and Creativity, 2021)
This research purpose was to describe the dress code role as the identity, creativity communication, creativity in service business organization. The research finding desribed that the higher level, mid level, and operational employees told that the uniform was part of their self’s and organization’s identity that was able to build thier proudness, to belong, to motivate in achievement, and to control their behavior. On the other hand, the customers told that the company’s uniform was representing their wish to get company’s primal service and trust. The recommendation from the employees on all levels and the customers were requiring a stylish, expensive-look, and creative, and changing the uniform periodically.